2019
DOI: 10.1038/s41573-019-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of 3′,5′-cyclic nucleotide phosphodiesterases: inhibition and beyond

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
310
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(315 citation statements)
references
References 353 publications
(374 reference statements)
3
310
0
2
Order By: Relevance
“…Although these dichotomous effects have not been studied systematically, it is likely that they arise due to the complexities involved in coordinating the recognized spatial and temporal selectivity of cellular cAMP signaling. Indeed, spatial and temporal compartmentation of cAMP signaling is made possible by the subcellular localization of the enzymes that synthesize cAMP (adenylyl cyclases), the enzymes that hydrolyze and inactivate cAMP (cyclic nucleotide phosphodiesterases; PDEs), and the dominant cAMP effectors (PKA and EPAC) [3,4,[10][11][12][13]. Other factors that likely contribute to the dichotomous effects of cAMP on cell migration involve the interdependence of the individual steps (i.e., cell adhesion, protrusion, and retraction) required for cells to move efficiently [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although these dichotomous effects have not been studied systematically, it is likely that they arise due to the complexities involved in coordinating the recognized spatial and temporal selectivity of cellular cAMP signaling. Indeed, spatial and temporal compartmentation of cAMP signaling is made possible by the subcellular localization of the enzymes that synthesize cAMP (adenylyl cyclases), the enzymes that hydrolyze and inactivate cAMP (cyclic nucleotide phosphodiesterases; PDEs), and the dominant cAMP effectors (PKA and EPAC) [3,4,[10][11][12][13]. Other factors that likely contribute to the dichotomous effects of cAMP on cell migration involve the interdependence of the individual steps (i.e., cell adhesion, protrusion, and retraction) required for cells to move efficiently [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphodiesterase (PDE) enzymes metabolize the intracellular second messengers cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP). The PDE superfamily of enzymes contains 11 gene families (PDE1 to PDE11), most of which contain several PDE genes (Baillie et al, 2019). PDE4 enzymes are a family of four genes (PDE4A-D) within the PDE superfamily which specifically hydrolyze the 3 ,5 phosphodiester bond of cAMP to yield 5 adenosine monophosphate (5 -AMP).…”
Section: Introductionmentioning
confidence: 99%
“…A potential approach to improve the therapeutic index of orally bioavailable PDE4 inhibitors is to direct the PDE4 subtype selectivity toward PDE4B which accounts for many of the anti-inflammatory effects (Ariga et al, 2004) and away from PDE4D which is related to emesis (Robichaud et al, 2002). It has been demonstrated that a non-subtype selective PDE4 inhibitor like roflumilast has a better therapeutic index that a PDE4D selective inhibitor like cilomilast (Baillie et al, 2019). Unfortunately, no selective PDE4B inhibitors have advanced to clinical trials (Fox et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With the importance of spatial and temporal compartmentalisation of cAMP signalling in health and disease well established, current research focusses on mapping cAMP signalling pathways in space and time across different cellular systems. Family-selective PDE inhibitors are FDA-approved for the treatment of congestive heart failure, thrombocythaemia, chronic obstructive pulmonary disease, psoriasis, psoriatic arthritis, atopic dermatitis, intermittent claudication, erectile dysfunction, and pulmonary arterial hypertension (Baillie et al, 2019). However, some of these therapeutic agents are associated with significant side effects which, at least in part, are causally linked to their inability to discriminate between isoforms within the same PDE family.…”
Section: Introductionmentioning
confidence: 99%